From the Criminalization of Substances to the “War on Drugs” Policy: A Century of Prohibitionism in Brazil - José Guilherme Magalhães e Silva; Luís Felipe Zilli; Letícia Godinho de Souza (Revista Direito GV)
Abstract In 1921, Decree 4,294 defined prohibitionism as the referential model of state response to drugs in Brazil. One century later, not only is the approach still enshrined in national legislation but also materialized in a complex institutional and bureaucratic network of governance and public policies. This paper examines the evolution of drug policies in Brazil over the past century, exploring how a web of normative, political, and institutional devices converged to entrench the hegemony of the prohibitionist approach in public responses to drugs. A systematic analysis of national and international legislation reveals that the prohibitionist enterprise was successful in Brazil due to two factors: i) as an ideational set, it was integrated into structuring discursive fields of Brazilian political culture, dialoguing with the stigmatization of marginalized populations and criminalization of their practices; and ii) as an ordering principle of public policy, it has demonstrated remarkable resilience and adaptability, incorporating elements of alternative models into its framework without compromising its fundamental structures. Political innovations implemented in Brazil since the 1990s (especially decriminalization and damage reduction models) have been able to neither shake the definition of drugs as a moral and criminal problem, nor prevent its instrumentalization as a policy of socio-spatial control of lower classes.